Rabbit haemorrhagic disease: virus persistence and adaptation in Australia. (14th August 2014) - Schwensow, Nina I.; Cooke, Brian; Kovaliski, John; Sinclair, Ron; Peacock, David; Fickel, Joerns; Sommer, Simone
Abstract In Australia, the rabbit haemorrhagic disease virus (RHDV) has been used since 1996 to reduce numbers of introduced European rabbits (Oryctolagus cuniculus) which have a devastating impact on the native Australian environment. RHDV causes regular, short disease outbreaks, but little is known about how the virus persists and survives between epidemics. We examined the initial spread of RHDV to show that even upon its initial spread, the virus circulated continuously on a regional scale rather than persisting at a local population level and that Australian rabbit populations are highly interconnected by virus‐carrying flying vectors. Sequencing data obtained from a single rabbit population showed that the viruses that caused an epidemic each year seldom bore close genetic resemblance to those present in previous years. Together, these data suggest that RHDV survives in the Australian environment through its ability to spread amongst rabbit subpopulations. This is consistent with modelling results that indicated that in a large interconnected rabbit meta‐population, RHDV should maintain high virulence, cause short, strong disease outbreaks but show low persistence in any given subpopulation. This new epidemiological framework is important for understanding virus–host co‐evolution and future disease management options of pest species to secure Australia's remaining natural biodiversity.